Genetic regulation of the achaete scute complex of Drosophila melanogaster. - del Prado, J.M.; Garcia-Bellido, A. (Wilhelm Roux's archives of developmental biology, 1984)
Mutants in two loci,hairy (h (+)) andextramacrochaetae (emc (+)), produce phenotypes corresponding to an excess of function of theachaete-scute complex (AS-C), that is, they cause the appearance of extra chaetae. These mutants, although recessive in normal flies, become dominant in the presence of extra doses of AS-C. Here we study the interactions between these three genes, in an attempt to elucidate their relationships. The results show that the insufficiency produced byh oremc mutants can be titrated by altering the number of copies of AS-C. Moreover, excess of function of AS-C produced by derepression mutants within the complex (Hairy-wing) can also be titrated by altering the number of wild type copies of(+) oremc (+). These specific interactions indicate that bothh (+) andemc (+) code for "repressors" of AS-C that interact with theachaete andscute region of the complex respectively.